Controlling the Formation Process of Methylammonium‐Free Halide Perovskite Films for a Homogeneous Incorporation of Alkali Metal Cations Beneficial to Solar Cell Performance. Issue 13 (15th February 2022) - Zheng, Daming; Zhu, Tao; Yan, Yanfa; Pauporté, Thierry
Abstract: Incorporating multiple cations of the 1A alkali metal column of the periodic table (K + /Rb + /Cs + ) to prepare perovskite films is promising for boosting photovoltaic properties but requires a uniform distribution. The effects of NH4 Cl additives and alkali metal cations (K + /Rb + /Cs + ) on the one‐step formation process of methylammonium‐free, formamidinium‐based, iodide perovskite films are analyzed in a step‐by‐step manner. NH4 Cl improves the solubility of PbI2 in solution by forming an intermediate and then favors the perovskite phase formation. Moreover, during the annealing process, this additive is shown to increase grain size, to improve crystallinity and to suppress PbI2 formation. K at low concentration is always homogeneously distributed across the film thickness. On the other hand, Cs is more concentrated at the surface and Rb in the depths of pristine films. With NH4 Cl additives, these two alkali metals are more homogeneously distributed because NH4 Cl slows down the movement of Cs + and Rb +, it changes the growth direction of the perovskite film, making the overall crystallization quality improved and the distribution more uniform. It results in perovskite films with large monolithic grains. Combined with a perovskite film surface treatment with n‐propylammonium iodide, a high stabilized power conversion efficiency of 22.04% is reached. Abstract : It is shown that an ammonium chloride additive in precursor solutions governs the even depth distribution of alkali metal (group 1A) elements in methylammonium‐free perovskites, favors crystallinity, and induces a lateral growth of large monolithic film grains. Combined with the surface treatment by n‐propylammonium iodide, it results in solar cells with high photovoltaic performance and improved stability.